Truth-tasting: aesthetic, normativity, and error - Pavoni, A. (Association for Philosophy & Literature Conference, 2019)
The obsessive quest for a truth where to settle and take refuge from the dislocation of existence grounds the suspicion for error and erring that traverses Western thought. While today the limits of this sedentary metaphysics have been widely addressed, the uncritical endorsement of nomadic wandering proves as much problematic, given its affinity with the normative and ethical flexibility of neoliberal politics and post-truth rhetorics. How to move beyond this impasse, in the direction of an ‘erring praxis’ able to elude the conservative will to truth, without surrendering to the anarchic celebration of errancy per se? The paper takes up this question, using taste as a tool to reconfigure in non-oppositional terms the aesthetic and normative relation between truth and error. Building on the work of Deleuze, Guattari and Agamben, this conceptual endeavour unfolds via an engagement with the philosophy of so-called Natural Wine Movement (NWM). This term loosely gathers diverse winemakers who did move a speculative, aesthetic and normative challenge to wine-politics, by means of disarticulating the making and the tasting of wine from both the hegemonic standards of traditional wine institutions, and the consumer-oriented branding of the market approach. By presenting the main, albeit by no means homogeneous conceptual and strategic tenets of NWM, the paper shows how its inherently materialist and non-human orientation contains the lineaments of a promising ethico-political praxis, one that does not naively endorse, but rather cultivates a relation with error; one that does not oppose or reject the given norms, but rather makes them err and wander otherwise, perverting the normative logic of the Same by generating an alternative normative apparatus that is open to the aberrant movements of the terroir, the non-human materiality of its constitution, and the eventful ‘truth’ of its taste. The argument will be presented both conceptually and sensorially.